2021
DOI: 10.1017/jns.2020.56
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of edible brown algae extracts for the inhibition of intestinal carbohydrate digestive enzymes involved in glucose release from the diet

Abstract: Type II diabetes is considered the most common metabolic disorder in the developed world and currently affects about one in ten globally. A therapeutic target for the management of type II diabetes is the inhibition of α- glucosidase, an essential enzyme located at the brush border of the small intestinal epithelium. The inhibition of α-glucosidase results in reduced digestion of carbohydrates and a decrease in postprandial blood glucose. Although pharmaceutical synthetic inhibitors are available, these are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Phenolic compounds and fucoidans are characterised as α-glucosidase inhibitors. 6,12,19 However, compared with other seaweeds, wakame has low polyphenols and fucoidans; therefore, its α-glucosidase inhibitory activity is likely weak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic compounds and fucoidans are characterised as α-glucosidase inhibitors. 6,12,19 However, compared with other seaweeds, wakame has low polyphenols and fucoidans; therefore, its α-glucosidase inhibitory activity is likely weak.…”
Section: Discussionmentioning
confidence: 99%
“…Someof these inhibitors are derived from seaweeds. 5,6 One meta-analysis reported that dietary fiber improved Undaria Pinnatifida (Wakame) Moderates Postprandial Glycaemia in Healthy Young Japanese Women fasting blood glucose concentrations in patients with type 2 diabetes. 7 However, the reported effects on fasting blood glucose concentrations have differed depending on the type of dietary fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Many seaweeds also exhibit inhibitory effects on α-glucosidase and α-amylase, such as Ascophyllum nodosum, Fucus vesiculosus, and Undaria pinnatifida [168,169]. Bioactive compounds from Ecklonia stolonifera and Eisenia bicyclis, including phlorotannin, showed inhibitory effects on protein tyrosine phosphatase 1 B (PTP1B) and α-glucosidase [174], whereas phlorotannin showed moderate inhibitory effects on rat lens aldose reductase (RLAR), human recombinant aldose reductase (HRAR), and PTP1B [10].…”
Section: Regulated Gene Expression Enriched the Abundance Of Gut Micr...mentioning
confidence: 99%
“…Alpha-glucosidase is one of the digestive enzymes, its main function is to accelerate the hydrolysis of polysaccharides (starch) to glucose (acts on (14) bonds) in order to promote glucose absorption and, therefore, raise blood glucose levels [58]. This helps to prevent hyperglycemia and maintain normal blood sugar levels by slowing down the digestion of starch and extra dietary carbohydrates [58].…”
Section: Alpha-glucosidasementioning
confidence: 99%